Differences in executive abilities rather than associative processes contribute to memory development. Issue 18 (12th October 2021) - Müller, Nils C. J.; Kohn, Nils; van Buuren, Mariët; Klijn, Nadia; Emmen, Helene; Berkers, Ruud M. W. J.; Dresler, Martin; Janzen, Gabriele; Fernández, Guillén
Abstract: Children's learning capabilities change while growing up. One framework that describes the cognitive and neural development of children's growing learning abilities is the two‐component model. It distinguishes processes that integrate separate features into a coherent memory representation (associative component) and executive abilities, such as elaboration, evaluation, and monitoring, that support memory processing (strategic component). In an fMRI study using an object‐location association paradigm, we investigated how the two components influence memory performance across development. We tested children (10–12 years, n = 31), late adolescents (18 years, n = 29), and adults (25+ years, n = 30). For studying the associative component, we also probed how the utilisation of prior knowledge (schemas) facilitates memory across age groups. Children had overall lower retrieval performance, while adolescents and adults did not differ from each other. All groups benefitted from schemas, but this effect did not differ between groups. Performance differences between groups were associated with deactivation of the dorsal medial prefrontal cortex (dmPFC), which in turn was linked to executive functioning. These patterns were stronger in adolescents and adults and seemed absent in children. Thus, the children's executive system, the strategic component, is not as mature and thus cannot facilitate memory performance in the same way as in adolescents/adults. In contrast, we did not find age‐related differences in the associative component; with activity in the angular gyrus predicting memory performance systematically across groups. Overall, our results suggest that differences of executive rather than associative abilities explain memory differences between children, adolescents, and adults. Abstract : In an fMRI study, we investigated whether memory differences between children, adolescents, and adults stem from developmental changes in executive abilities, the strategic component, or rather from differences in mechanisms related to binding different features together into a memory representation, the associative component. Overall, our results suggest that differences of executive rather than associative abilities explain memory differences between children, adolescents and adults.